m(m-2)=24

Simple and best practice solution for m(m-2)=24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m(m-2)=24 equation:


Simplifying
m(m + -2) = 24

Reorder the terms:
m(-2 + m) = 24
(-2 * m + m * m) = 24
(-2m + m2) = 24

Solving
-2m + m2 = 24

Solving for variable 'm'.

Reorder the terms:
-24 + -2m + m2 = 24 + -24

Combine like terms: 24 + -24 = 0
-24 + -2m + m2 = 0

Factor a trinomial.
(-4 + -1m)(6 + -1m) = 0

Subproblem 1

Set the factor '(-4 + -1m)' equal to zero and attempt to solve: Simplifying -4 + -1m = 0 Solving -4 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1m = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1m = 0 + 4 -1m = 0 + 4 Combine like terms: 0 + 4 = 4 -1m = 4 Divide each side by '-1'. m = -4 Simplifying m = -4

Subproblem 2

Set the factor '(6 + -1m)' equal to zero and attempt to solve: Simplifying 6 + -1m = 0 Solving 6 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1m = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1m = 0 + -6 -1m = 0 + -6 Combine like terms: 0 + -6 = -6 -1m = -6 Divide each side by '-1'. m = 6 Simplifying m = 6

Solution

m = {-4, 6}

See similar equations:

| 5(3n+1)=7(6n+9)+2 | | x^2-2x-5=30 | | -22=n-16 | | 0.9x^2+5.4x-4=0 | | z-1=4(7z-4) | | 0=16x^2+8x+1 | | 5v+3=18 | | 3a(3a+2a-7)= | | 220=0,22.x | | w^2+2wj-35j^2= | | 3x^2+15x-3=0 | | 220=1,1.x | | x^2+9x-90= | | -12y-14=142 | | 2x+3x+1=7x-11 | | 5-(4+2x)=2x+8 | | x^2+19x+12=-48 | | -y(5y-3y+2y)= | | 220=2,2.x | | 5(2n+3)=6(7n+4)+9 | | x^2-21x+108= | | 5n^2+19n-68=-2 | | 10x^2-69x+100=-19 | | x^2-25x+144= | | 0=2x^2+16x-34 | | 91=1000.c | | 3m(4+m)= | | 36y^2-36=0 | | 48x+8+3x-6=90 | | 91=100.c.10 | | 15-x=2+1+x+x | | 10x^2+55x=-75 |

Equations solver categories